Practising critical reflection a resource handbook - Fook, Jan; Gardner, Fiona (Maidenhead New York Open University Press, 2007)
Focuses on a description and analysis of the theoretical input as well as the approach involved in critical reflection. his work also demonstrates some skills, strategies and tools which might be used to practise it. It is suitable for students across social work, and health sciences as well as health care and social welfare professionals.
Part I. The theory and contexts of critical reflection -- 1. The context for professionals -- 2. Clarifying our approach to critical reflection -- 3. The theoretical frameworks underlying critical reflection -- Part II. The process of critical reflection -- 4. The critical reflection model and process -- 5. Introductory session -- 6. The second session (stage 1) -- 7. The third session (stage 2) -- 8. The benefits and outcomes of critical reflection -- Part III. Application of the critical reflection process -- 9. Using critical reflection in organizational settings -- 10. Using critical reflection in research and evaluation -- 11. Critical reflection and direct practice -- 12. Ongoing issues.
Includes bibliographical references and index.
Keywords: Human services -- Philosophy; Self-knowledge, Theory of; Critical thinking